Irradiated Non-replicative Lactic Acid Bacteria Preserve Metabolic Activity While Exhibiting Diverse Immune Modulation - Porfiri, Luca; Burtscher, Johanna; Kangethe, Richard T.; Verhovsek, Doris; Cattoli, Giovanni; Domig, Konrad J.; Wijewardana, Viskam (Frontiers in Veterinary Science, 2022)
In recent years, safety concerns regarding the administration of probiotics led to an increased interest in developing inactivated probiotics, also called “paraprobiotics”. Gamma-irradiation represents a promising tool that can be used to produce safe paraprobiotics by inhibiting replication while preserving the structure, the metabolic activity and the immunogenicity of bacteria. In this study, we evaluated the ability of four strains of lactic acid bacteria (LAB: Lacticaseibacillus casei, Lactobacillus acidophilus, Lactiplantibacillus plantarum and Lacticaseibacillus paracasei) in preserving the metabolic activity and the immune modulation of swine porcine peripheral blood mononuclear cells, after gamma irradiation or heat inactivation. Our results show that all four strains retained the metabolic activity following gamma irradiation but not after heat inactivation. In terms of immune modulatory capacity, irradiated L. acidophilus and Lc. paracasei were able to maintain an overall gene expression pattern similar to their live state, as heat inactivation did with Lc. casei. Moreover, we show that the two inactivation methods applied to a same strain, can induce an opposed expression of key genes involved in pro-inflammatory response (e.g. IFN-alpha and Interleukin-6 for Lc. casei), whereas gamma irradiation of L. acidophilus and Lc. paracasei was able to induce a down-regulation of the anti-inflammatory TGF-beta. Taken together, our data show that immune modulation can be impacted not only by different inactivation methods but also by the strain of LAB selected. This study highlights that gamma irradiation harbors the potential to produce safe non-replicative metabolically active LAB and identifies immunomodulatory capacities that may be applied as vaccine adjuvants.